A polar system of intercontinental bird migration - Alerstam, Thomas; Bäckman, Johan; Gudmundsson, Gudmundur A.; Hedenström, Anders; Henningsson, Sara; Karlsson, Håkan; Rosén, Mikael; Strandberg, Roine (Proceedings of the Royal Society B: Biological Sciences, 2007)
Studies of birdmigration in the Beringia region of Alaska and eastern Siberia are of special interest for revealing the importance of bird migration between Eurasia and North America, for evaluating orientation principles used by the birds at polar latitudes and for understanding the evolutionary implications of intercontinental migratory connectivity among birds as well as their parasites. We used tracking radar placed onboard the ice-breaker Oden to register bird migratory flights from 30 July to 19 August 2005 and we encountered extensive birdmigration in the whole Beringia range from latitude 64 degrees N in Bering Strait up to latitude 75 degrees N far north of Wrangel Island, with eastward flights making up 79% of all track directions. The results from Beringia were used in combination with radar studies from the Arctic Ocean north of Siberia and in the Beaufort Sea to make a reconstruction of a major Siberian-American birdmigration system in a wide Arctic sector between longitudes 1108 E and 130 degrees W, spanning one-third of the entire circumpolar circle. This system was estimated to involve more than 2 million birds, mainly shorebirds, terns and skuas, flying across the Arctic Ocean at mean altitudes exceeding 1 km (maximum altitudes 3-5 km). Great circle orientation provided a significantly better fit with observed flight directions at 20 different sites and areas than constant geographical compass orientation. The long flights over the sea spanned 40-80 degrees of longitude, corresponding to distances and durations of 1400-2600 km and 26-48 hours, respectively. The birds continued from this eastward migration system over the Arctic Ocean into several different flyway systems at the American continents and the Pacific Ocean. Minimization of distances between tundra breeding sectors and northerly stopover sites, in combination with the Beringia glacial refugium and colonization history, seemed to be important for the evolution of this major polar bird migration system.